Separating the coherence transfer from chemical shift evolution in high‐resolution pure shift COSY NMR. (11th April 2018) - Aguilar, Juan A.; Belda, Raquel; Gaunt, Benjamin R.; Kenwright, Alan M.; Kuprov, Ilya
Abstract : Recent developments in data sampling and processing techniques have made it possible to acquire 2‐dimensional NMR spectra of small molecules at digital resolutions in both dimensions approaching the intrinsic limitations of the equipment and sample on a realistic timescale. These developments offer the possibility of enormously increased effective resolution (peak dispersion) and the ability to effectively study samples where peak overlap was previously a limiting factor. Examples of such spectra have been produced for a number of 2‐dimensional techniques including TOCSY and HSQC. In this paper, we investigate some of the problems in applying such techniques to COSY spectra and suggest a modification to the classic experiment that alleviates some of these problems. Abstract : We propose an experiment (PSYCOSY) that allows us to acquire COSY spectra that are homonuclear decoupled in f1, and that have very high digital resolution in f1, while retaining control of the coherence evolution.